The Profile of Saudi Nursing Workforce: A Cross-Sectional Study - Mohammad Alboliteeh; Judy Magarey; Richard Wiechula (Hindawi Limited, 2017)
Introduction. The Royal Monarchy in Saudi Arabia decreed that all sectors of the workforce would be subject to a policy of "Saudisation" to reduce the reliance on the expatriate workforce and to reduce the unemployment rate of Saudi nationals (Al-Mahmoud et al., 2012). Methodology. A cross-sectional design was chosen to investigate the research questions. The population of this study comprised Saudi Registered Nurses working in MOH hospitals in Riyadh which is the main health care provider in Saudi Arabia (Aboul-Enein, 2002; MOH, 2009). Results and Findings. A total number of 1,198 questionnaires were distributed and 61.2% (n=741) were returned. The findings of the study showed that the questionnaires were collected from an equal portion of the study locale and that a sample of 741 is enough to create a strong conclusion and answer the problem set in this study and all the questions in the study have been provided with answers with enough data and literatures to supports its findings. Conclusion and Recommendations. The results indicate that an increase in the recruitment of Saudi males may simply reflect cultural issues such as gender specific facilities and the Saudisation program's nondiscriminatory approach to employment of both genders into nursing.